Developments in Russian politics - Lankina, Tomila; Hale, Henry E. 1966-; Johnson, Juliet 1968- (London Bloomsbury Publishing Academic, 2024)
"The 10th edition of this go-to-text offers critical discussion of contemporary Russian politics and its fundamental principles. It covers established topics such as executive leadership, parties and elections, and also newer issues of national identity, protest, and Russia and Greater Eurasia. Taking a bottom-up approach, Developments in Russian Politics analyses the political system in which Putin's influence can be understood and covers frequently overlooked topics like informal economy, climate change, and gender"-- Provided by publisher.
Preface / Henry E. Hale, Juliet Johnson, and Tomila Lankina -- Putin and the dynamics of Russia's political system / Henry E. Hale -- Russian imperial and soviet history / Kristy Ironside -- The long reach of history / Tomila Lankina -- Nationalism, identity, and war / Gulnaz Sharafutdinova -- Russia's gendered politics / Valerie Sperling -- Russia's economic policies / Juliet Johnson -- Russia's informal economy / Yoshiko Herrera and Evgeniya Mitrokhina -- Formal institutions of government / Grigorii V. Golosov -- Authoritarian mechanics / David Szakonyi -- Federalism and center-periphery relations / Vladimir Gel'man -- Chechnya / Marat Iliyasov -- Marginalized groups / Jeremy Morris -- Protest and civil society / Katerina Tertytchnaya -- Climate change / Debra Javeline -- Russia and Ukraine / Maria Popova and Oxana Shevel -- Russian foreign policy / Kathryn Stoner.
Includes bibliographical references (pages 317-342) and index.
Keywords: Russia (Federation) -- Politics and government -- 1991-.